Simple and promising paper-based electrochemical platform for serological detection of American tegumentary leishmaniasis - Barraza, Daniela Estefanía (2024)
BACKGROUND American tegumentary leishmaniasis (ATL) is an endemic neglected tropical disease (NTD), its conventionaltreatment is toxic, slow, and invasive. Rapid diagnosis is crucial for the clinical management of suspected patients, so thedevelopment and use of low-cost, miniaturised and portable devices could be the key.OBJECTIVES This work aimed to develop a simple paper-based electrochemical platform for the serological detection of ATL. METHODS Platform was fabricated in Whatman N°1 paper, contains a hydrophobic zone generated by wax printing, two pencilgraphite electrodes, and uses specific crude extracts (CA) antigens for ATL immuno-determination. The platform performancewas analysed by measuring the relative impedance change for different antigen-antibody combinations. Then, 10 serum humansamples previously diagnosed by the gold standard (five positive ATL cases and five non-ATL cases) were evaluated. FINDINGS The platform presented a linear response for the charge transfer resistance (ΔRct) and the interface reactance (ΔXc).Also, optimal working conditions were established (1/60 serum dilution and 180 μg/mL CA concentration). Then, the platformpermits to distinguish between ATL and non-ATL (p < 0.05) human serum samples. MAIN CONCLUSIONS Our platform could allow the diagnosis, management, and monitoring of leishmaniasis while being anextremely simple and environmentally friendly technology.